EVALUATION OF BLEACHING ON A CAD/CAM HYBRID CERAMIC MATERIAL - CULIC, Bogdan; GASPARIK, Cristina; VARVARĂ, Adrian Mihai; CULIC, Carina; DRAGOȘ, Cristian Mihai; SILAGHI DUMITRESCU, Laura; DUDEA, Diana (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The objective of our study was to test the bleaching effect of two whitening gels, on stained hybrid ceramic material used for Computer Aided Design/ Computer Aided Manufacturing technology. 40 rectangular specimens 12/14/1mm were prepared from Vita Enamic blocks. All specimens were accelerated stained, and distributed in two groups. Group 1 was bleached using Opalescence PF 15% (Ultradent, USA), group 2 was bleached using an experimental gel containing natural products. ΔE* (used to assess the color changes) was above the perceptibility threshold of 1.2 in 40%; and the WID (used to assess the bleaching process in dentistry) showed high units for both bleaching gels. Hybrid ceramics staining showed moderate results, while the bleaching effect was present, with no statistical difference between the discolorations produced by the two bleaching gels (p<0.05). SEM images showed that the bleaching gels did not affect the surface structure of the material.